Anesthesia on Pediatric Laproscopy - Wiryana, Made; Sinardja, I Ketut; Kurniyanta, Putu; GdeAgung Senapathi, Tjokorda; Gede Widnyana, I Made; Utara Hartawan, I Gusti Agung Gede; Parami, Pontisomaya; Darma Junaedi, I Made; Putra Pradhana, Adinda (Bali Journal of Anesthesiology, 2017)
Laparoscopic surgery has several advantages compared to a regular surgical procedures. This technique can reduce the stress of surgery, reduce the need for postoperative analgesia, decreased respiratory and wound complications, lowering long hospitalization, including in the intensive therapy, and the patient can go back to eat quickly. The magnitude of changes in vital signs that occur will be influenced by the patients age, cardiovascular function, and anesthetic agents are used. Physiological changes in pediatric laparoscopic surgery were similar to adults. Children have a higher vagal tone and sometimes a stimulus to the peritoneum by insufflation gas or penetration laparoscopic and trocar can lead to bradycardia and asystole. Intra-abdominal pressure is an important determinant for maintaining cardiovascular stability during laparoscopy. Adequate relaxation needed during the duration of the surgery.